Proposta de um reator rápido de pequeno porte para geração de energia - Mauricio Gilberti (2015)
The 4S Reactor (Super Safe, Small and Simple Reactor) developed by Toshiba Corporation and the Central Research Institute of Electric Power Industry-CRIEPI Japan, was extensively studied and analyzed their operating characteristics in this work. Through of the a equivalent corereactor model were determined and evaluated the neutronics parameters such as reactivity coefficients, fuel evolution and burnup, the reactor efficiency and performance over the operating cycle. The developed reactor model was able to adequately represent the project and determine the core operating characteristics. From these results, a series of changes in the project were executed based on new conceptsoptimization from the standpoint of improving the performance and core reactivity coefficients. The results demonstrate that there is a huge space for optimization of the project allowing remodel the core and reactor as characteristics desired of the efficiency and of the intrinsic parameters of core security. All study was performed using nuclear code MCNPX 2.6.0.